Successful Management of Pseudo-Ludwig Angina from Supratherapeutic Warfarin Use: A Case Report - Utku Ekin; Arham Hazari; Nizar Alyassin; Alan Alcantara; Moh’d Hazem Azzam; Mourad Ismail (Clinical Practice and Cases in Emergency Medicine)
Introduction: Ludwig angina is a potentially fatal condition characterized by soft tissue infection of the submandibular, sublingual, and submental compartments. Pseudo-Ludwig angina is a rare condition characterized by sublingual swelling of non-infectious etiology, typically in the setting of supratherapeutic anticoagulation. However, other etiologies, such as angioedema and trauma, have been described. Case Report: We present the case of a 59-year-old female with pseudo-Ludwig angina that developed in the setting of warfarin therapy and supratherapeutic international normalized ratio. She presented with sublingual swelling and dysphagia. She was successfully treated with dexamethasone, vitamin K, and fresh frozen plasma. The most appropriate imaging modalities in these cases are contrast-enhanced computed tomography (CT) and CT angiogram. If a hematoma is present, antibiotics for anaerobic coverage are also appropriate. Conclusion: We hope this case sheds light upon this rare pathology and ultimately hastens recognition and proper intervention.